(3JZQjO GdYfOdjH Ydi ZUf GdCfOdS GdQWjHs - (3jhSa Hf eMeO GdTgjQ Hf Gdhcjd Gdejdhis; (3GdebQj , CMeO Hf eMeO Hf CMeO Hf jMji GdJdeSGfj, CHh GdYHGS,J (B1041 (3g` s ((3eMeO cfhf GdaGSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JaQO HGdOhGe hGdHbGA , hMce Ydi ef ShGg HGdRhGd hGdafGA s
(3BNQgG (B:s
(3hhGab GdaQGZ ef JMQjQg ai jhe GdCMO GdeHGQc SGOS TgQ Pi GdbYOI NJGe SfI CQHY YTQI heGFI HYO GdCda ef GdgLQI GdfHhjI s
(3GdeDda Jhai HYO SfI (B1114(3g`s
(3GdNW HYVg eVHhWs
(3GNJUQg ELGHI MSjf CafOi Hf HQgGf GdOjfs
(3hgh GNJUGQ faM GdWjH ddebQj s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdJGQjNs